Regional Problems of Labour Productivity Rise (illustrated by the Krasnodar area) - T. P. Khokhlova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article deals with researching the problem of labour productivity rise in the Krasnodar area as a key factor of attaining sustainability and further development of the region economy. Based on dynamic analysis the indexes of labour productivity in Russia, federal area and some entities of the Russian Federation were compared and principle trends and factors of labour productivity drop in the Krasnodar area were identified. It was shown that low, in comparison with the leading entities, labour productivity acts as the major reason for reducing the rate of social and economic development in the area. The authors analyze the content of the strategic program ‘Labour Productivity Rise’ elaborated in the context of the principle project ‘Smart Kuban – Leaders of the Future’ in order to implement the Strategy of social and economic development of the Krasnodar area up to 2030. Key factors of strategic development and approaches to increasing efficiency and labour productivity in the area were identified, including those that can be attained at the expense of technical re-equipment of labour, introduction of advanced methods and technologies, scientific and innovative measures and improving material incentives of workers. The use of all these methods can provide synergy effect that will ensure sustainable development of economic potential of the region.